Targeting CXCR1 alleviates hyperoxia-induced lung injury through promoting glutamine metabolism - Hao Qin; Wei Zhuang; Xiucheng Liu; Junqi Wu; Shenghui Li; Yang Wang; Xiangming Liu; Chang Chen; Hao Zhang (Cell Reports, 2023)
Summary: Although increasing evidence suggests potential iatrogenic injury from supplemental oxygen therapy, significant exposure to hyperoxia in critically ill patients is inevitable. This study shows that hyperoxia causes lung injury in a time- and dose-dependent manner. In addition, prolonged inspiration of oxygen at concentrations higher than 80% is found to cause redox imbalance and impair alveolar microvascular structure. Knockout of C-X-C motif chemokine receptor 1 (Cxcr1) inhibits the release of reactive oxygen species (ROS) from neutrophils and synergistically enhances the ability of endothelial cells to eliminate ROS. We also combine transcriptome, proteome, and metabolome analysis and find that CXCR1 knockdown promotes glutamine metabolism and leads to reduced glutathione by upregulating the expression of malic enzyme 1. This preclinical evidence suggests that a conservative oxygen strategy should be recommended and indicates that targeting CXCR1 has the potential to restore redox homeostasis by reducing oxygen toxicity when inspiratory hyperoxia treatment is necessary.